ANALISIS SISTEM PENYELENGGARAAAN MAKANAN DI INSTALASI GIZI RUMAH SAKIT UMUM DAERAH (RSUD) KOTA TANGERANG - Khoirul Anwar; Elza Nanda Ersella; Juwita Cahaya Permana; Fitri Ayuningsih; Lutfi Dhiyah Ulhaq; Miftahul Jannah; Sri Irawati (Jurnal Mitra Kesehatan, 2023)
Hospital food preparation management is a series of activities that begin with menu preparation, food requirements planning, budget planning, food procurement, receiving and storage, food preparation, distribution, storage, reporting, and evaluation. The purpose of this study is that researchers want to know the description of the implementation of nutrition activities which include planning, procurement, reception, storage, processing, and distribution of food to patients in the nutrition department of Regional Hospitals (RSUD). Tangerang. Hospital nutrition services (PGRS) including patient nutrition services are a series of activities to fulfill the nutritional needs of patients through disease-appropriate food. The implementation of hospital nutrition services was adapted from the 2013 Hospital Nutrition Service Guidelines (PGRS) for patient nutrition in hospitals. The type of research used by program managers in organizing food service at Tangerang City Hospital is descriptive research. The subjects of this study were recruited from the nutrition division of patients at Tangerang City General Hospital. This study used questionnaires and observations to collect data. 52.9% of respondents thought that the tasks and work skills were appropriate, around 52.9% of respondents felt comfortable at work and about 41.2% of respondents thought it was good if the warehouse provided an opportunity for employees to rest. Part of the planning process, where there are several assumptions according to the guidelines for Hospital Nutrition Services (PGRS), where there are availability menus, instruction menus, item menus, food ingredients to be processed, food processing equipment, and quality control. rules and standards of use.